Effects of obstacle structures on the movement and deposition of debris flows in storage basins - Wanyu Zhao; Yong You; Xiaoqing Chen; Wenrong Cui; Jiangang Chen (Geomatics, Natural Hazards & Risk)
Storage basins are among the main engineering measures used in debris flow mitigation engineering, but many storage basins lack engineering measures for decreasing the velocity and dissipating the energy of debris flows. Therefore, it is necessary to construct obstacles in storage basins to decrease the velocity and dissipate the energy of debris flows. However, the influence of obstacles on the movement and deposition characteristics of debris flows is not clear. Experiments were performed to investigate the effects of obstacles on the movement and deposition of debris flows. Obstacles caused debris flows to spread laterally, and obstacles with square cross sections were particularly conducive to the lateral spreading of debris flows. Compared with obstacles with round and square cross sections, diversion of debris flows by obstacles with triangular cross sections was relatively minor. Additionally, obstacles reduced the mud marks height of debris flows. The maximum mud marks height of debris flows decreased with decreasing spacing between obstacles, and the maximum height can be reduced by a large amount. The effect was greater for obstacles with square cross sections than other shapes. Thus, obstacles with square cross sections should be preferred for use in structures in storage basins for debris flows.